Structure Engineered High Piezo‐Photoelectronic Performance for Boosted Sono‐Photodynamic Therapy - Zhang, Rui; Yang, Dan; Zang, Pengyu; He, Fei; Gai, Shili; Kuang, Ye; Yang, Guixin; Yang, Piaoping (Advanced materials (Weinheim), 2024)
Sono‐photodynamic therapy is hindered by the limited tissue penetration depth of the external light source and the quick recombination of electron–hole owing to the random movement of charge carriers. In this study, orthorhombic ZnSnO3 quantum dots (QDs) with piezo‐photoelectronic effects are successfully encapsulated in hexagonal upconversion nanoparticles (UCNPs) using a one‐pot thermal decomposition method to form an all‐in‐one watermelon‐like structured sono‐photosensitizer (ZnSnO3@UCNPs). The excited near‐infrared light has high penetration depth, and the watermelon‐like structure allows for full contact between the UCNPs and ZnSnO3 QDs, achieving ultrahigh Förster resonance energy transfer efficiency of up to 80.30%. Upon ultrasonic and near‐infrared laser co‐activation, the high temperature and pressure generated lead to the deformation of the UCNPs, thereby driving the deformation of all ZnSnO3 QDs inside the UCNPs, forming many small internal electric fields similar to isotropic electric domains. This piezoelectric effect not only increases the internal electric field intensity of the entire material but also prevents random movement and rapid recombination of charge carriers, thereby achieving satisfactory piezocatalytic performance. By combining the photodynamic effect arising from the energy transfer from UCNPs to ZnSnO3, synergistic efficacy is realized. This study proposes a novel strategy for designing highly efficient sono‐photosensitizers through structural design. The design of watermelon‐like ZnSnO3@UCNPs (upconversion nanoparticles) heterostructure can effectively prevent the degradation of piezoelectric ZnSnO3 quantum dots in tumor environment, fully utilizing its piezoelectric catalytic effect as an antitumor carrier. Combined with the photodynamic therapy effect arising from the energy transfer from UCNPs to ZnSnO3, a satisfactory therapeutic efficacy is realized.